ANALISIS FAKTOR KEJADIAN TB PARU DI KABUPATEN BUTON TENGAH - Arimaswati Arimaswati; Sukrianto Halik; Tety Yuniarty Sudiro; La Ode Kardin; Nina Indryani Nasruddin (NHM PRESS, 2022)
Pulmonary tuberculosis is a contagious disease caused by Mycobacterium tuberculosis. Tuberculosis transmission can be obtained from environmental factors and behavioral factors. This study aims to determine the factors associated with the incidence of pulmonary tuberculosis in Distric Buton Tengah. observational analytic using cross sectional study approach. The number of samples used in this study were 84 samples selected by the simple proportional startified random sampling method. The results of the data obtained were processed using Univariate and Bivariate analysis with the Chi-Square statistical test with a p value <0.05 and equipped with a test to see the level of closeness of the relationship of each variable studied. Nutritional status variable with p value = 0.004 and r value = 0.345, occupancy density variable with p value = 0.000 and r = 0.430, household contact history variable with p value = 0.000 and r = 0.408 value had a relationship with the incidence of pulmonary tuberculosis. The BCG immunization history variable with a p value of 0.179 and a value of r = 0.145, had no relationship with the incidence of pulmonary tuberculosis. The conclusion of this study is nutritional status, occupancy density and household contact history are factors that are associated with the incidence of pulmonary tuberculosis in District Buton Tengah. history of BCG immunization is a factor that is not related to the incidence of pulmonary tuberculosis in District Buton Tengah.